INDICACIONES DE CATETERISMO CARDÍACO / Cardiac catheterization indications - Francisco L Moreno-Martínez; Julio C Echarte-Martínez (CorSalud, 2009)
The cardiac catheterization makes possible the accurate diagnosis of diseases in the arteries, valves and heart cavities; as well as any malformation that may exist. In many occasions it is also possible to implement the necessary treatment. This procedure is carried out in order to confirm the presence of any kind of heart disease because it constitutes the golden test in Cardiology and is useful in determining the extension and intensity of the disease. This article tries to summarize in a didactic way the diagnostic and therapeutic indications of cardiac catheterization.